Social Network Analysis of Alzheimer’s Teams: A Clinical Review and Applications in Psychiatry to Explore Interprofessional Care - Lazzari, Carlo; Kotera, Yasuhiro; Green, Pauline; Rabottini, Marco (Current Alzheimer Research, 2021)
Introduction: Understanding the social networks of professionals in psychiatric hospitals and communities working with Persons With Alzheimer’s (PWA) disease helps tackle the knowledge management in patient care and the centrality of team members in providing information and advice to colleagues. Objectives: To use Social Network Analysis (SNA) to confirm or reject the hypothesis that psychiatric professionals have equal status in sharing information and advice on the care of PWA and have reciprocal ties in a social network. Methods: The sample consisting of 50 psychiatric professionals working in geriatric psychiatry in the UK completed an anonymous online survey asking them to select the professional categories of the colleagues in the interprofessional team who are most frequently approached when providing or receiving advice about patient care and gathering patient information. SNA is both a descriptive qualitative analysis and a quantitative method that investigates the degree of the prestige of professionals in their working network, the reciprocity of their ties with other team members, and knowledge management. Results: The social network graphs and numerical outcomes showed that interprofessional teams in geriatric psychiatry have health carers who play central roles in providing the whole team with the knowledge necessary for patient care; these are primarily senior professionals in nursing and medical roles. However, the study reported that only 13% of professionals had reciprocal ties with knowledge sharing within teams. Conclusion: The current research findings show that knowledge management in interprofessional teams caring for PWA is not evenly distributed. Those with apparently higher seniority and experience are more frequently consulted; however, other more peripheral figures can be equally valuable in integrated care.
Keywords: Alzheimer' s disease